Glucosylglycerate is an osmotic solute and an extracellular metabolite produced by Streptomyces caelestis - Pospíšil, Stanislav; Halada, Petr; Petříček, Miroslav; Sedmera, Petr (Folia microbiologica, 2007)
Streptomyces caelestis DSM 40084 produces two osmolytes, viz. 2-O-(alpha-D-glucopyranosyl)-zeta-glyceric acid (GG) and trehalose. Both compounds were isolated and identified by nuclear magnetic resonance spectroscopy and mass spectrometry. A very sensitive regulation of the cell osmolytes was demonstrated in exponentially growing cultures. The intracellular levels of GG and trehalose increased 2x in response to a step change of medium osmolarity caused by 0.3% NaCl. 1H NMR analysis of the cell extracts did not confirm the presence of additional osmolytes. GG is a S. caelestis metabolite commonly released from the cells; its concentration reached 3 g/L during the cultivation in a yeast extract--(NH4)2SO4-glycerol medium. This is the first report on the occurrence of the ionic osmolyte GG in the genus Streptomyces and on its free excretion to the medium.
Keywords: Spectrometry, Mass, Electrospray Ionization; trehalosa; kyseliny glycerové; Trehalose; hmotnostní spektrometrie s elektrosprejovou ionizací; Research Support as Topic; extracelulární tekutina; Extracellular Fluid; finanční podpora výzkumu jako téma; Glyceric Acids; Streptomyces